Sugar production in Java and in the Philippines during the nineteenth century - Wolters, Willem G. (Philippine Studies, 1992)
During the nineteenth century the sugar industry in Java and the Philippines showed strongly divergent patters of development due to a number of reasons. In the early decades of the century the point of departure for the two colonial industries was rather similar. In both colonies cane cultivation, and sugar processing was carried out in the traditional way, with primitive technology and sugar mills that were knows as the Chinese type. In Java, technological innovations were introduced in the course of the century, leading to the intensification of the production process. Consequently the numbers of mill increased slowly from about 70 in the late 1830s to about 100 in 1870 and about 190 in 1900. Sugar mills enlarged their area of cane cultivation and the production of sugar in tons per factory per year increased from about 700 in the late 1830s to almost 3,000 by the end of the century.